PANDANGAN MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING UNIVERSITAS KATOLIK WIDYA MANDALA MADIUN TERHADAP KESEHATAN REPRODUKSI WANITA - Widodo, Bernardus (Educatio Vitae, 2016)
Reproductive health problem becomes crucial in human life. Every human person without exception have the same right to fight for his health. The students as the future generation has many advantages intellectually, as well as a reformer agent needs to have a view comprehensively associated with female reproduction and impact. Weak maintain reproductive health and misconceptions result from improper sources of information about female reproduction, increasing the likelihood of cases of sexually transmitted diseases (STDs). This study aims to find a picture of the view of students of guidance and counseling Widya Mandala Madiun University on reproductive health. The method used in this research is qualitative descriptive paradigm-interpretatip. The research sample of 40 students of guidance and counseling. Data is collected using questionnaires and interviews are limited. Data in the form of questionnaires were analyzed with analysis techniques mean, and interviews described as a form of  strengthen the analytical results. The results showed that 85% of the students have learned about reproductive health. It can be seen from three aspects that are the focus in this research that aspect of premarital sex with a mean of 4.55 (good category once), aspects of abortion mean 6.89 (excellent category) and aspects of infectious diseases (STDs) with a mean of 3.56 ( excellent category). Furthermore, from the results of limited interviews students found keeping kesehataan female reproduction is essential to prevent sexually transmitted diseases (STDs), and as much as 88% of their agreed if at Widya Mandala Catholic University Madiun, which has a course guidance and counseling established service bureau services counseling services including consultation on women's reproductive health.Key Words: reproduction health, premarital sex, abortion, sexually transmitted diseases (STDs)